Investigating the Air Transport-Induced EKC Hypothesis: Evidence from NAFTA Countries - Dursun, Erdal (International Journal of Energy Economics and Policy, 2022)
The Major goal of this manuscript is to evaluate the long run relationship of economic growth, energy consumption, CO2 emissions and air transportation within the context of EKC hypothesis. In this sense, ADF and PP unit root tests, FMOLS, DOLS, CCR and ARDL tests are performed in order to determine the coefficient of effects of independent variables on dependent variable CO2 emissions. The periods from 1970 to 2020 for variables are derived from World Banks and Ourworldindata official website as annual data. According to FMOLS, DOLS, CCR tests there is a long-term stable linkage between CO2 emissions and energy consumption from 1970 to 2020 for all NAFTA countries including USA, Canada, and Mexico which is demonstrated empirically. It can be interpreted that increased consumption of the non-renewable energy or fossil will increase the amount of carbon dioxide emissions. For this reason, all three countries need to benefit from more environmentally friendly renewable energy sources.